2003
DOI: 10.1017/s1461145703003377
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of amisulpride on the pharmacokinetics and safety of lithium

Abstract: Lithium may be used as adjuvant therapy in schizophrenic patients and antipsychotics can be employed during the early phases of lithium therapy in patients with bipolar disorder. The issue of interactions between lithium and antipsychotics is therefore important. This study investigates the potential influence of repeated administration of amisulpride, an atypical antipsychotic, on the pharmacokinetics of lithium at steady state. Twenty-four healthy male volunteers (aged 1833 yr) received lithium carbonate (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the present study, lithium co-medication was reported in only 2.5% of patients and showedin some contrast to the results of Bergemann, et al (2004) no substantial influence on dose-corrected ASU plasma levels. Several other factors, which could have influenced the renal elimination of ASU (Canal, et al, 2003;Bergemann, et al, 2004;, had, however, not been excluded in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, lithium co-medication was reported in only 2.5% of patients and showedin some contrast to the results of Bergemann, et al (2004) no substantial influence on dose-corrected ASU plasma levels. Several other factors, which could have influenced the renal elimination of ASU (Canal, et al, 2003;Bergemann, et al, 2004;, had, however, not been excluded in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ASU shows only a low plasma protein binding affinity (16%), almost no interaction with hepatic cytochrome P450 dependent enzymes, and is renally eliminated to a very great extent without metabolites (Caccia, 2000;2002). Dose-adjustment has to take place in patients with renal insufficiency (Caccia, 2000); however, potential interactions with other renally eliminated substances (e.g., lithium) have not been reported unequivocally (Canal, et al, 2003;Bergemann, et al, 2004). In healthy elderly volunteers aged 65-79, a single oral dose of ASU 50 mg showed a pharmacokinetic profile similar to that of young subjects (Hamon-Vilcot, et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the current lithium dose regimen is mainly for bipolar disorder therapy, which generally needs high serum concentrations and therefore has a narrow therapeutic window of 0.6-1.2 mmol/L and a maintenance therapy window of 0.6-0.8 mmol/L (Methaneethorn and Sringam, 2019). The PK properties of lithium treatment in adults have been reported previously (Wing et al, 1997;Canal et al, 2003;Wong et al, 2011), but studies on the PKs of lithium in young pediatric patients are rare. One PK study in nine children aged 10-12 years and diagnosed with behavioral disorder or adjustment disorder receiving a single dose of 300 mg lithium carbonate suggested that the PK parameters were similar to those of adults, except for the higher total clearance in children (Vitiello et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Lithium influences on neurochemical processes proceeding in a brain [3]. It is established, that lithium ions are able to stop acute maniac excitation, and it may be used as adjuvant therapy in schizophrenic patients [4][5][6]. Lithium is still the first drug of choice for treatment of affective disorders [7,8].…”
Section: Introductionmentioning
confidence: 99%